2023
DOI: 10.3390/children10050810
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir Efficacy and Tolerability in Children with COVID-19-Associated Allergic Comorbidities such as Asthma, Allergic Rhinitis, and Atopic Dermatitis

Abstract: In children, coronavirus disease 2019 (COVID-19) starts as a minor illness compared to adults, but during the ongoing COVID-19 pandemic, distinct SARS-CoV-2 variants and subvariants have changed options for therapies in both adults and children, especially for those with comorbidities such as allergies. On 25 April 2022, Remdesivir (RDV), a viral RNA-dependent RNA polymerase inhibitor, was approved by the Food and Drug Administration (FDA) for the treatment of pediatric patients 28 days and older, weighing ≥3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In some cases, modified transaminase levels can linger or appear tardively, leading to some cases being diagnosed as post-COVID immune hepatitis [ 21 ]. Although considered generally safe for use, Remdesivir was used in pediatric patients as treatment, and it was observed that one important side effect is the elevation of both AST and ALT [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, modified transaminase levels can linger or appear tardively, leading to some cases being diagnosed as post-COVID immune hepatitis [ 21 ]. Although considered generally safe for use, Remdesivir was used in pediatric patients as treatment, and it was observed that one important side effect is the elevation of both AST and ALT [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research into novel therapeutic approaches, including repurposing existing drugs, developing antiviral agents, and harnessing innovative immunomodulatory strategies, holds immense promise. Yet, few studies in the selected lot contained explicit laboratory marker data in patients treated with antiviral drugs [ 67 , 98 ]. While both studies looked into the effects of Remdesivir, one followed its efficacy in children, where the authors noticed elevated transaminase, CRP, LDH, prothrombin time, anemia, and lymphopenia according to COVID severity at the beginning of the treatment, concluding that transaminase levels and prothrombin time were elevated after the Remdesivir intake, which were considered secondary effects of the treatment [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of remdesivir was also correlated with a reduced need for invasive mechanisms of additional oxygen administration. Less than a quarter of patients required an increase in oxygen support while receiving remdesivir [ 12 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our geographical area, one paper analyzed the use of remdesivir in children. The study was performed in Bucharest and showed that the use of remdesivir in the treatment of COVID-19 in children was not associated with serious adverse reactions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%